Could a remarkable decrease in leptin and insulin levels from colostrum to mature milk contribute to early growth catch-up of SGA infants? - Marina Nunes; Clécio Homrich da Silva; Vera Lucia Bosa; Juliana Rombaldi Bernardi; Isabel Cristina Ribas Werlang; Marcelo Zubaran Goldani; NESCA Group (BMC, 2017)
Abstract Background Breast milk is known to contain many bioactive hormones and peptides, which can influence infant growth and development. In this context, the purpose of this study was to evaluate the influence of different clinical pregnancy conditions on hormone concentrations in colostrum and mature breast milk. Methods An observational study was performed with mother-newborn pairs divided into five groups according to maternal clinical background: diabetes (12), hypertension (5), smoking (19), intrauterine growth restriction of unknown causes with small-for-gestational-age newborns at delivery (12), and controls (21). Socioeconomic data, anthropometric measurements and breast milk samples were collected between the first 24 and 48 h and 30 days postpartum. Leptin, adiponectin, and insulin levels in breast milk were measured by immunoassays. Results A significant decrease in leptin (p = 0.050) and insulin (p = 0.012) levels from colostrum to mature breast milk in mothers of small-for-gestational-age infants was observed. Maternal body mass index was correlated with both leptin and insulin, but not with adiponectin. Insulin levels were negatively correlated to infant weight gain from birth to one month (p = 0.050). In addition, catch-up growth was verified for small-for-gestational-age infants throughout the first month of life. Conclusions This study suggests that a remarkable decrease in leptin and insulin levels in mature milk of mothers of small-for-gestational-age newborns may be involved in the rapid weight gain of these newborns. The physiological and external mechanisms by which these significant decreases and rapid weight gains occur in this group remain to be elucidated.